Perancangan Sistem Informasi Bimbingan Akademik Pada Program Studi Teknik Arsitektur Universitas Sebelas Maret Surakarta - sugimin, sugimin (Indonesian Journal of Information Technology and Computing (IMAGING), 2023)
The task of the Academic Supervisor is to develop student achievement, assist in lecture activities and provide consultation on both academic and non-academic issues. The problem faced by Academic Supervisor Lecturers at the Architectural Engineering Study Program, Sebelas Maret University Surakarta (UNS) is to arrange the schedule of academic guidance. This has an impact on academic guidance activities being irregular so that student progress can be monitored. In order to improve the quality of students both in terms of hard skills and soft skills, academic guidance activities must run regularly. Based on the description of the problem, the authors formulate the problem to be solved in this study is "How to design an academic guidance information system in the UNS Architectural Engineering Study Program". The author determines that the problem in this research is the design of an academic guidance information system only for the scope of the UNS Architectural Engineering Study Program. The method used to design an academic guidance information system uses the System Development Life Cycle (SDLC) with the Waterfall model. The academic guidance information system is designed using the PHP Native programming language. As a data storage media the author uses a MySQL database. With the design of this online academic guidance information system, it is hoped that student development can be monitored so that student quality improvements can be realized.